Aerial art, the new landscape of Robert Smithson - Pico, Ramón (Journal of Architecture and Urbanism, 2019)
Aircraft were to play a decisive role in the short career of Robert Smithson. In 1969, when he published his article Aerial Art, Walther Prokosch, an architect specializing in aviation, put him in contact with TAMS engineering. This gave rise to his involvement in a land altering operation as vertiginous and brutal as the construction of Dallas Fort-Worth International Airport. At that point Smithson became aware of the human capacity to transform Mother Earth and the importance of contemplation from the air. He incorporated these interests into his artistic creation, thus paving the way for earthwork, crucial to the evolution of Land Art. The study of the documents included among Robert Smithson’s Papers at the Smithsonian Museum of American Art allows us to reconstruct a history that shared interests and concerns with Moholy-Nagy’s New Vision or Le Corbusier’s Loi du Méandre.First published online 15 January 2020